Les légumineuses pour des systèmes agricoles et alimentaires durables - Schneider , Anne; Huyghe , Christian (éditions Quae, 2015)
What do we know about inputs and potential of legumes in terms of the sustainability of agricultural and food systems? How can they be used to reduce the damage and maximise the benefits for the environment, agriculture and man? This reference work fuels the reflection on protein sources, nitrogen management in France and the relationship between legumes and sustainability.